Anti-Pilling Properties of Polyester-Cotton Blend using Plasma and Chemical Finish - Adil Hussain; Reamsha Khan (Journal of Design and Textiles, 2024)
Plasma treatment is an effective, efficient, and environment- friendly technology which is currently being used to modify the surface of textile substrate and its chemical structure. However, limited research has been conducted regarding the influence of plasma technology on the characteristics of blends. This project throws light on the effect of plasma treatment on  the pilling properties of polyester-cotton blends. In cold plasma, different reactive species interact with substrate surface. The cleaning, modification, and coating processes are dependent upon the parameters (e.g., plasma source and imput voltage). There are three main mechanisms involved in plasma treatment, that is,  radical formation, attachment of functional groups, deposition/polymerization, and the etching process. Maximum resistance to pill formation may be achieved using the plasma treatment on the p/c blend.